Institutional development as a tool for economic growth and social and environmental development (Revista LIDER, 2020)
This paper intends to offer a reflection on the institutional development as a tool for economic growth and social and environmental development of communities and peoples. The method used is that of critical analysis to determine the scope of the concepts, theories and empirical research findings to determine the impact on local institutional development and support the delineation of the processes of institutionalization and institutional change. It is concluded that institutional development should be integrated with other forms of development showing a coherent strategic intervention that calls for cooperation changes of corporate culture that require sustained implementation processes in political support and participation of stakeholders involved.